Resource partitioning for Integrated Modular Avionics: comparative study of implementation alternatives. (6th August 2013) - Han, Sanghyun; Jin, Hyun‐Wook
ABSTRACT Most current generation avionics systems are based on a federated architecture, where an electronic device runs a single software module or application that collaborates with other devices through a network. This architecture makes the software development process very simple, but the hardware system becomes very complicated and it is difficult to resolve issues of size, weight, and power efficiently. An integrated architecture can address the size, weight, and power issues and provide better software reusability, testability, and reliability by means of partitioning. Partitioning provides a framework that can transparently integrate several real‐time applications on the same computing device, allowing the isolation of the execution environment in terms of resources and faults. Several studies on partitioning software platforms have been reported; however, to the best of our knowledge, extensive comparison and analysis of design and implementation alternatives have not been conducted owing to the extreme complexity of their implementation and measurement. In this paper, we present three design alternatives for partitioning at the user, kernel, and virtual machine monitor levels, which are compared quantitatively. In particular, we target the worldwide standard software platform for avionics systems, that is, Aeronautical Radio, Incorporated Specification 653 (ARINC 653). Overall, our study provides valuable design references and demonstrates the characteristics of design alternatives. Copyright © 2013 John Wiley & Sons, Ltd.